Characterization of lesions of the breast with Proton MR Spectroscopy: Comparison of Carcinomas, Benign Lesions, and Phyllodes Tumors - Tse, Gary; Abdul Samad, Humairah; Pang, Lai-Man; Chu, Winnie; Law, Bonita Ka Bo; Kung, Fred Y.L; Yeung, David K.W (American Roentgen Ray Society, 2003)
OBJECTIVE. Proton MR spectroscopy is a recently described technique with high sensitivity and specificity for differentiating breast carcinoma from benign lesions. We evaluated the possible relationship between spectroscopy results and the tumor proliferative index, angiogenesis, and HER2/neu oncogene overexpression. SUBJECTS AND METHODS. We prospectively evaluated 19 breast carcinomas, 21 benign breast lesions (including 18 fibroadenomas, one fibrocystic change, one hamartoma, and one papilloma), and six phyllodes tumors (four benign, two of borderline malignancy) using proton MR spectroscopy. All lesions were larger than 1.5 cm. Tumor Ki-67 proliferative index, tumor angiogenesis, and HER2/neu oncogene overexpression were evaluated by immunohistochemistry of the histologic material. RESULTS. Spectroscopy findings were positive in 17 (89%) of 19 carcinomas but negative for all benign lesions and phyllodes tumors (sensitivity, 89%; specificity, 100%). Significantly higher levels were obtained for all biologic parameters in carcinomas compared with benign lesions and phyllodes tumors. HER2/neu oncogene overexpression was present in 37% of carcinomas but not in other lesions. The two false-negative findings of breast carcinoma showed similar Ki-67 proliferative index and microvessel density compared with the remaining carcinomas, but both cases were negative for HER2/neu overexpression. CONCLUSION. Proton MR spectroscopy is useful in the in vivo characterization of breast masses when the lesion exceeds 1.5 cm in maximal dimension. Spectroscopy is unable to reveal benign breast lesions and phyllodes tumors of benign and borderline malignancy. We suggest that a false-negative spectroscopic result may be related to an absence of HER2/neu overexpression in carcinoma of the breast.